Loss of m6A demethylase ALKBH5 promotes post‐ischemic angiogenesis via post‐transcriptional stabilization of WNT5A. Issue 5 (1st May 2021) - Zhao, Yongchao; Hu, Jingjing; Sun, Xiaolei; Yang, Kun; Yang, Lebing; Kong, Lingqiu; Zhang, Beijian; Li, Fuhai; Li, Chaofu; Shi, Bei; Hu, Kai; Sun, Aijun; et al.
Abstract: Background: Post‐ischemic angiogenesis is critical for blood flow recovery and ischemic tissue repair. N6‐methyladenosine (m6A) plays essential roles in numerous biological processes. However, the impact and connected mechanism of m6A on post‐ischemic angiogenesis are not fully understood. Methods: AlkB homolog 5 (ALKBH5) was screened out among several methyltransferases and demethylases involved in dynamic m6A regulation. Cardiac microvascular endothelial cells (CMECs) angiogenesis and WNT family member 5A (WNT5A) stability were analyzed upon ALKBH5 overexpression with adenovirus or knockdown with small interfering RNAs in vitro. The blood flow recovery, capillary, and small artery densities were evaluated in adeno‐associated virus (AAV)‐ALKBH5 overexpression or ALKBH5 knockout (KO) mice in a hind‐limb ischemia model. The same experiments were conducted to explore the translational value of transient silencing of ALKBH5 with adenovirus. Results: ALKBH5 was significantly upregulated in hypoxic CMECs and led to a global decrease of m6A level. ALKBH5 overexpression further reduced m6A level in normoxic and hypoxic CMECs, impaired proliferation, migration, and tube formation only in hypoxic CMECs. Conversely, ALKBH5 knockdown preserved m6A levels and promoted angiogenic phenotypes in hypoxic but not in normoxic CMECs. Mechanistically, ALKBH5 regulated WNT5A expression through post‐transcriptional mRNA modulation in an m6A‐dependent manner, which decreased its stability and subsequently impeded angiogenesis in hypoxic CMECs. Furthermore, ALKBH5 overexpression hindered blood flow recovery and reduced CD31 and alpha‐smooth muscle actin expression in hind‐limb ischemia mice. As expected, ALKBH5‐KO mice exhibited improved blood flow recovery, increased capillary, and small artery densities after hind‐limb ischemia, and similar beneficial effects were observed in mice with transient adenoviral ALKBH5 gene silencing. Conclusion: We demonstrate that ALKBH5 is a negative regulator of post‐ischemic angiogenesis via post‐transcriptional modulation and destabilization of WNT5A mRNA in an m6A‐dependent manner. Targeting ALKBH5 may be a potential therapeutic option for ischemic diseases, including peripheral artery disease. Abstract :